2010
DOI: 10.1152/jn.00551.2010
|View full text |Cite
|
Sign up to set email alerts
|

Selective Activation of Neuronal Targets With Sinusoidal Electric Stimulation

Abstract: Electric stimulation of the CNS is being evaluated as a treatment modality for a variety of neurological, psychiatric, and sensory disorders. Despite considerable success in some applications, existing stimulation techniques offer little control over which cell types or neuronal substructures are activated by stimulation. The ability to more precisely control neuronal activation would likely improve the clinical outcomes associated with these applications. Here, we show that specific frequencies of sinusoidal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
140
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(155 citation statements)
references
References 58 publications
14
140
1
Order By: Relevance
“…In a comparison between 20 Hz sinusoidal and square-wave stimulation, square-wave thresholds were 22.8±35.5% higher, lending further credence to reports that sine wave stimulation preferentially elicits responses in RGCs whilst avoiding axonal activation (12,13). A subsequent human psychophysical comparison suggested that percepts to sinusoidal stimulation were round and confined, in contrast to the elongated arcs perceived with squarewave stimulation.…”
supporting
confidence: 64%
“…In a comparison between 20 Hz sinusoidal and square-wave stimulation, square-wave thresholds were 22.8±35.5% higher, lending further credence to reports that sine wave stimulation preferentially elicits responses in RGCs whilst avoiding axonal activation (12,13). A subsequent human psychophysical comparison suggested that percepts to sinusoidal stimulation were round and confined, in contrast to the elongated arcs perceived with squarewave stimulation.…”
supporting
confidence: 64%
“…This point should be clarified in future studies with the application of more specific frequency ranges (e.g., 40 -60 Hz vs 80 -100 Hz). In this respect, studies have shown that different classes of neurons are activated at different frequencies (Freeman et al, 2010). Because different cortical areas contain different neuronal types, a specific band of frequencies might lead to the response of a subpopulation of neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few authors suggest stimulation by sinusoidal and conventional waveforms [9]- [11]. Reported TES does not use biological waveforms or typical membrane potential to stimulate.…”
Section: Methodsmentioning
confidence: 99%